The Problem of the Conscience Clause of Healthcare Professionals in Italy in the Years 2017-2020 - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2020)
The main goal of the article is to analyse the key elements of the living will in Italy and present the dispute regarding the understanding of the conscience clause of healthcare professionals. In the country on the Tiber, a law on the living will was passed in 2017. A living will consists in the anticipatory expression of ‘will’, by an adult or legal guardian acting in full possession of their mental faculties, concerning the possible administration or discontinuation of certain medical therapies in the future. The conscience clause, on the other hand, means the right to refuse to take such actions, which a particular person considers to be contrary to their personal convictions. The Italian law on the living will does not contain a provision on the conscience clause. For this reason, an ethical and legal problem arose for healthcare professionals, who refused to comply with the wishes of their patients for moral or religious reasons, for example by discontinuing artificial hydration or nutrition, thus, leading to the patient’s death. The ethical and legal dispute in Italy is part of a contemporary global debate on conscience clauses, euthanasia, assisted suicide, human rights, and the dignity of human life. Analyses have shown that healthcare professionals should be guaranteed the right, not to perform such medical procedures, which are contrary to their moral and religious convictions.